Feasibility Analysis of The Bribin Pump-As-Turbine in Semanu District, Gunungkidul Regency - Anggi Rahmawati; Agus Maryono; Muhammad Sulaiman (Proceeding of International Joint Conference on UNESA, 2025)
The 2025–2034 Electricity Supply Business Plan (RUPTL) prioritises the development of renewable energy based on base load technology, such as hydroelectric power plants (PLTA) and pumped storage systems. A similar pumped storage concept was previously introduced through a collaborative initiative between Germany and Indonesia, involving the Karlsruhe Institute of Technology (KIT) and the University of Giessen. The project, known as Indonesian Integrated Water Resources Management (IWRM), began in 2004 in the karst region of Gunung Kidul, Special Region of Yogyakarta. This project implemented a pump-as-turbine system in Bribin Cave to supply clean water to rural communities, with financial support from the German Federal Ministry of Education and Research (BMBF) within the framework of international collaborative research. However, in 2017, the Bribin PAT system was damaged by Cyclone Cempaka, rendering it inoperable. This study aims to assess the feasibility of revitalising PAT Bribin II through technical and economic analysis, while maintaining the original module design with a module configuration that is estimated to produce a water flow of 100 litres per second. The economic evaluation is based on estimated indicators such as Net Present Value (NPV), Internal Rate of Return (IRR), and Benefit-Cost Ratio (BCR). The findings show that the NPV remains positive and the BCR exceeds one at discount rates of 10%, 11%, 12%, and 13%, indicating the project's feasibility. This analysis confirms that the benefits exceed the costs. Overall, this study shows that the Bribin PAT revitalisation project is financially feasible and is expected to provide a solid foundation for policymakers to increase the benefits of Bribin PAT II in various financing scenarios.